Sculpture of Vishnu - 014. - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ This is a form of Lord Vishnu as we can identify from the Shankha (conch shell) in the top right hand and Chakra (discuss) in the top left hand. Bottom right hand is holding a beaded chian and the bottom left hand is broken.